2019
DOI: 10.1002/ijgo.12949
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of serum D‐dimer,CA125, and neutrophil‐to‐lymphocyte ratio in differentiating ovarian cancer and endometriosis

Abstract: Objective: To assess the utility of hematologic, inflammatory, and immunologic biomarkers for differentiating between ovarian cancer and endometriosis.Methods: Data were retrospectively reviewed from women diagnosed with ovarian cancer and endometriosis after ovarian cyst surgery in Zhejiang, China, 2014 Serologic and hematologic biomarkers, including white blood cell count, lymphocyte count, neutrophil count, red blood cell count, hemoglobin, platelets, and D-dimer, albumin, globulin, cancer antigen 125 (CA12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 26 publications
0
15
0
2
Order By: Relevance
“…When the cutoff value of the D-dimer was increased to 981 ng/mL, it was found the survival period of the above group was significantly lower than the below group, and the increase of the cut-off value of the D-dimer to 981 ng/mL may be an important clinical indicator to evaluate the prognosis of patients with advanced NSCLC. D-dimer, as the degradation product of fibrinolytic protein, reflects whether the body's internal fibrinolytic system is abnormal, and the high content of d-dimer in plasma is closely related to the poor prognosis of patients with advanced NSCLC (20), breast cancer (26), ovarian cancer (27), pancreatic cancer (28) and colon cancer (29). However, in this study, it was found that the original cut-off value of 500 ng/mL as D-dimer could not adequately assess the prognosis of advanced NSCLC patients and the enhance of its cut-off value was firmly related to the survival of advanced NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…When the cutoff value of the D-dimer was increased to 981 ng/mL, it was found the survival period of the above group was significantly lower than the below group, and the increase of the cut-off value of the D-dimer to 981 ng/mL may be an important clinical indicator to evaluate the prognosis of patients with advanced NSCLC. D-dimer, as the degradation product of fibrinolytic protein, reflects whether the body's internal fibrinolytic system is abnormal, and the high content of d-dimer in plasma is closely related to the poor prognosis of patients with advanced NSCLC (20), breast cancer (26), ovarian cancer (27), pancreatic cancer (28) and colon cancer (29). However, in this study, it was found that the original cut-off value of 500 ng/mL as D-dimer could not adequately assess the prognosis of advanced NSCLC patients and the enhance of its cut-off value was firmly related to the survival of advanced NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that the D-dimer level increased in 73% stage I ovarian cancer patients, whereas CA-125 increased in only 33%, so D-dimer is more sensitive in stage I ovarian cancer patients (46). Moreover, a previous study showed that D-dimer is a useful marker in differentiating ovarian cancer and endometriosis, with a sensitivity of 93.2% and a specificity of 87.5% (47). Therefore, the inclusion of D-Dimer was expected to improve the accuracy in identifying the subtypes of ovarian cancer.…”
Section: Further Optimizationmentioning
confidence: 97%
“…Moreover, the quantification of white blood cells (WBCs), lymphocytes, monocytes, neutrophils and platelets from full blood counts were found to be closely correlated with disease status and outcome. In addition, several combinatorial parameters, such as lymphocyte-to-monocyte ratio (LMR), fibrinogen-to-albumin ratio (FAR), platelet-to-lymphocyte ratio (PLR), and neutrophil-to-lymphocyte ratio (NLR) have been identified as prognostic biomarkers in several malignancies, including ovarian cancer [14][15][16]. If these parameters could be integrated into a model to formulate a tool to predict malignancy in ovarian masses, it would be useful to improve the therapeutic plans and surgical options for patients with ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%